Characterization of the clinical conditions and echocardiographic parameters of pulmonary pressure in dogs with degenerative valvular disease - Muñoz-Giraldo, Paula A. (2019)
Pulmonary hypertension (PH) is common in dogs with degenerative valvular disease (DVD) and is caused by an increase in left atrial pressure and pulmonary venous pressure. Cardiac catheterization is considered the gold standard for the diagnosis of PH. Tricuspid regurgitation (TR), measured by Doppler echocardiography, is commonly used in the clinic to determine the pressure gradient (PG) of TR reflecting pulmonary arterial systolic pressure (PAP). For the characterization of the echocardiographic parameters of pulmonary pressure in canines with DVD, 161 echocardiographic cases and the respective clinical histories of the patients admitted to the Veterinary Cardiology Unit of the city of Bogotá in a period of 8 months (November 2016 - June 2017) were evaluated. All patients diagnosed with DVD were grouped within the classification of the American College Veterinary Internal Medicine (ACVIM), and some essential criteria were evaluated to assign patients to the study group. None of the patients had a primary or secondary disease of cardiopulmonary origin, different from the one already mentioned. Echocardiographic parameters associated with the presentation of PH were taken and statistical analyses were carried out to determine the frequency of presentation, relevance and importance of each of these parameters with the development of the disease. In conclusion, the highest percentage of patients diagnosed with PH were classified as B2 within the ACVIM, which suggests that this group of patients has a greater possibility of presenting PH and, therefore, a greater possibility of congestion. No relevant data were found regarding the altitude of the city (>2600 m above the sea level).